Individual and organizational mindfulness: a social exchange-based approach. Issue 2 (28th June 2021) - Bagchi, Soumendra N.; Sharma, Rajeev
Abstract : Purpose: Understanding multiple dimensions of problem or opportunity and the context in an evolving environment is an essential task for leaders. The allied expectation is to be aware of gaps in knowledge, and areas of organizational ignorance, which can prove detrimental for the organization. In this paper, we propose a framework based on social exchange theory directed towards developing organizational mindfulness. Design/methodology/approach: This paper is a reflective note based on workshops conducted for senior managers of a Fortune Global 500 petrochemical company having more than 10, 000 employees. The workshop was carried out in modular mode, with one module conducted in virtual mode and the second module in physical mode. The time gap between each module was two months. Findings: Purposive questioning, engaged in both as a social exchange as well as to solicit information from multiple stakeholders which may otherwise would have been ignored, develops broader and more detailed analysis of problems and extensive individual and organizational mindfulness. Practical implications: This paper offers a methodology for managers to explore and develop solutions for complex problems. The methodology also provides identification of areas requiring organizational re-learning. Originality/value: This paper contributes to the literature on problem solving by providing a methodology to develop individual and organizational mindfulness. The structured format of the approach ensures this can be formalized and taught to decision makers, without being limited by their prior background.